SISTEM INFOMASI RAPORT ONLINE SD NEGRI 044852 BUKIT BERBASIS WEB - Jan Eperaim Pinem; Ertina Sabarita; Jenni Veronika Br Ginting (UPPM, 2019)
Design of Information System for Reporting Value-Based Raport in SD Negeri 044852 Bukit is asystem designed to manage values online. The value processing will be better if there are facilitiesfor students to check grades online, so that the delivery of value information to students will be faster.In conducting research, the author uses the descriptive method, which is looking for any problemsthat occur during the study.